The Application of Classical Guidance Based on Problem-Based Learning to Improve Students' Positive Emotions - Senia Pradirga Lasambouw (Universitas Negeri Medan, 2025)
This study aims to determine the application of classical guidance services based on Problem Based Learning in improving the positive emotions of seventh grade students at SMP Negeri 5 Percut Sei Tuan. This study uses the Guidance and Counseling Action Research method in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 30 students exhibiting symptoms of low positive emotions, such as low self-confidence, decreased motivation to learn, and low academic optimism. The instrument used was a Likert scale questionnaire. The measurement results showed an increase in the average score from 58.25 on the pre-test to 66.50 on the post-test of Cycle I, and further increased to 76.50 on the post-test of Cycle II. These findings demonstrate that classical guidance services based on Problem-Based Learning are effective in enhancing students' positive emotions, both individually and in groups. This study recommends the Problem-Based Learning method as a contextual, reflective, and collaborative approach to support the psychological well-being of students at the junior high school level.